4CPS-050 Conformity of antibiotic therapy duration in patients with febrile neutropenia, hospitalised in the haematology department of a university hospital. (24th March 2020) - Ravey, M; Robert, S; Henard, S; Demore, B
Abstract : Background and importance: The emergence of bacterial resistance and the proper use of antibiotics are major public health issues. In 2011, the European Conference on Infections in Leukaemia (ECIL) published recommendations for the management of febrile neutropenia. In this context, a university hospital wanted to evaluate follow-up of these recommendations. Aim and objectives: To evaluate conformity for duration of antibiotic therapy in patients with febrile neutropenia, hospitalised in the haematology department. Material and methods: The study was monocentric, retrospective, observational and conducted over a 6 month period in the haematology department. Data collection was carried out via a collection form. Two algorithms, created with the ECIL guidelines, were used to evaluate febrile neutropenia episodes. Duration of the prescription was considered to conform if it satisfied the following criteria: for undocumented infection, discontinuation of probabilistic antibiotic therapy at 72 hours of apyrexia; for documented infection, continuation of documented antibiotic therapy, according to the recommendations of the local antibiotic guidelines. Results: Ninety infectious episodes were studied. The study population comprised 49 men (54%) and 41 women (46%). Average age was 56 years. Cefepime or piperacillin/tazobactam were systematically introduced as probabilistic therapy. If the infection was undocumented (n=61/90), the duration of probabilistic antibiotic therapy conformed in 41% of cases (n=25/61). For clinical documentation (n=6/90), the conformity rate was 67% (n=4/6). For microbiological documentation (n=23/90), compliance rate was 74% (n=17/23). Conclusion and relevance: For most undocumented infections, probabilistic antibiotic therapy was prescribed for too long. This may be explained by the fragility of haematology patients and the fear of being confronted with recurrence of infection. For documented infections, conformity was very satisfying, as haematologists have extensive knowledge of infectiology. In order to harmonise prescription duration and continue to prevent the emergence of bacterial resistance, a guide for correct use of antibiotics and a second prospective study should be considered. References and/or acknowledgements: No conflict of interest.